GW24-e1158 Aliskiren/amlodipine versus aliskiren/hydrochlorothiazide in hypertension: Indirect-comparison meta-analysis of randomised controlled trials. (1st October 2013) - DengFeng, Gao; Yang, Liu; Xiaolin, Niu; Rui, Yan; Zhe, Meng
Abstract : Objectives: Aliskiren, a direct renin inhibitor, is effective for reducing blood pressure (BP) in patients with hypertension when combined with a calcium channel blocker such as amlodipine or a diuretic such as hydrochlorothiazide (HCTZ). However, the efficacy and tolerability between the 2 combinations are unclear. We performed a systematic review of randomised controlled trials of aliskiren/amlodpine and aliskiren/HCTZ for hypertension. Methods: The Cochrane Central Register of Controlled Trials, MEDLINE, Embase and the Novartis clinical trial database were searched through December 2012 for reports of RCTs of aliskiren/amlodpine and aliskiren/HCTZ versus monotherapy in patients with hypertension. The main outcome measures were reduction in systolic BP (SBP) and diastolic BP from baseline and rates of therapeutic response and BP control. Tolerance of aliskiren/amlodipine and aliskiren/HCTZ was also analysed. Outcomes were initially pooled by standard random-effects methods, producing a weighted mean difference (WMD) or risk ratio (RR) and 95% confidence intervals (95% CIs). The pooled estimates were then used for adjusted indirect comparisons. Results: We selected 19 reports of trials involving 13, 614 participants. Aliskiren/amlodpine and aliskiren/HCTZ were more effective than monotherapy in controlling BP. Aliskiren/amlodipine was significantly more effective than aliskiren/HCTZ in reducing SBP (WMD -3.36 mmHg, 95% CI -4.64–2.07 mmHg) and DBP (-3.49 mmHg, -4.34–2.63 mmHg). As compared with aliskiren/HCTZ, alikiren/amlodipine was associated with higher rate of therapeutic response (RR 1.23, 95% CI 1.14–1.33) and BP control (RR 1.24, 1.11–1.39). Number of adverse events and withdrawals due to adverse events were similar with aliskiren/amlodipine and aliskiren/HCTZ. Conclusions: BP control is better with aliskiren combined with amlodipine or HCTZ than with monotherapy, aliskiren/amlodipien being more effective than aliskiren/HCTZ.